Yeast dynamin interaction with ESCRT proteins at the endosome. (19th March 2017) - Banh, Bryan T.; McDermott, Hyoeun; Woodman, Sara; Gadila, Shiva Kumar Goud; Saimani, Uma; Short, John C. W.; Kim, Kyoungtae
Abstract: The dynamin‐like protein, Vps1, is a GTPase involved in cargo sorting and membrane remodeling in multiple cellular trafficking pathways. Recently, Vps1 has been shown to genetically interact with ESCRT subunits. We tested the hypothesis that the functional connection of Vps1 with some of these subunits of ESCRT complexes occurs via a physical interaction. By utilizing the yeast two‐hybrid system, we revealed that Vps1 physically interacts with the ESCRT‐II subunits, Vps22 and Vps36, and the ESCRT‐III subunit Vps24. We found that Vps1 and ESCRT‐II components colocalize with Pep12, an endosomal marker. Additionally, loss of Vps1 or depletion of the GTPase activity of Vps1 results in a moderate defect in Cps1 targeting to the vacuole. Here, we discussed the potential implications of Vps1 and ESCRT interaction and their roles in the endosome‐to‐vacuole traffic. In summary, yeast dynamin interacts with ESCRT II and III complexes, and it functions in Cps1 trafficking toward the vacuole.